MIGS as a Simple and Efficient Method for Gene Silencing in Rice - Zheng, Xuelian; Yang, Lijia; Li, Qian; Ji, Linyi; Tang, Aiting; Zang, Lili; Deng, Kejun; Zhou, Jianping; Zhang, Yong (Frontiers in Plant Science, 2018)
MiRNA-induced gene silencing (MIGS) technology is a special kind of RNA interference technology that uses miR173 to mediate the production of trans-acting siRNA (ta-siRNA) to achieve target gene silencing. This technique has successfully mediated the silencing of interested genes in plants such as Arabidopsis, tobacco, petunia, etc. In order to establish the MIGS technology system in monocots such as rice, we constructed the MIGS backbone vectors pZHY930, pZHY931, pZHY932 and pZHY933 with different with promoters to regulate the expression of miR173 and miR173_ts. The rice OsPDS reporter gene was selected to compare the efficiency of four MIGS backbone vectors by the ratio of albino plants. The results showed that all the four backbone vectors could effectively mediate the target gene silencing, and pZHY932 showed highest efficiency up to 90%. Through MIGS silencing of endogenous OsROC5 and OsLZAY1 in rice, we successfully obtained rice mutant plants with rice leaf roll and tillering angles increasing, and further confirmed that MIGS backbone vector can efficiently mediate target gene silencing in rice. On the other hand, in order to verify the efficiency of MIGS-mediated multi-gene silencing in rice, we constructed two double-gene silencing vectors OsPDS & OsROC5, OsPDS & OsLZAY1, based on pZHY932 backbone vector. Double mutant rice plants with increased leaf and albino tiller angles. And we successfully obtained bladed leaf albino seedling and increased tillering angle albino seedling double-silencing mutations. We further constructed a MIGS-OsGBSS gene silencing vector and obtained rice materials with significantly reduced amylose content. This result indicated that MIGS could be an efficient method in monocots gene silencing and gene function analysis.